Kontrol Diri dan Prokrastinasi Akademik dalam Menyelesaikan Skripsi pada Mahasiswa - Fitri Ramdani; Asniar Khumas; Nurfitriany akhri; Sahril Buchori (Seminar Nasional LP2M UNM, 2022)
Abstract. This study aims to determine the relationship between self-control and academic procrastination in completing thesis in IAIN Bone students. This research uses quantitative methods. The subjects in this study were taken using the Accidental Sampling technique, namely 209 active students at IAIN Bone who had taken more than eight semesters and were currently programming a thesis. The results of hypothesis testing in this study used Spearman's rho. The results show a correlation coefficient of r = -0.757 with a significant value of p = 0.000 (p <0.05) meaning that there is a negative relationship between self-control and academic procrastination in completing theses for IAIN Bone students. The value of the correlation coefficient shows a negative value, which means that self-control with academic procrastination is negatively correlated and is in a very strong category. This research contributes to the thinking and development of behavioral science treasures, especially in the fields of social psychology and educational psychology. Keywords: Self Control, College Student, Academic Procrastination